Pelatihan BUDIKDAMBER ( Budidaya Ikan Dalam Ember) Untuk Suplai Protein Mandiri Di Kelurahan Tipes Kota Surakarta - Frendika Yusuf Putra Nugraha; Hernowo Ardy Prasetyo; Siti Hajar Nur Khasanah; Reva Evia Noraida; Naning Setiani; Marjam Desma Rahadhini (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
Aproblems in urban areas, this is because in addition to limited residential land but food needs also increase significantly. Meanwhile, agricultural output is getting lower because a lot of land is converted for infrastructure development. The use of the home yard as a cultivation land is one of the efforts that can be done by the community in meeting pagan needs mandri. Fish farming in buckets is one of the systems of cultivating plants as well as fish on narrow land by utilizing buckets as a cultivation medium. The result obtained by the service partner is to be able to harvest catfish and kangkong after two to three months of treatment.